Resynchronizing estrus and ovulation in open cows and heifers - Tiffany, S.M.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We compared outcomes of two protocols used to resynchronize estrus and ovulation in dairy females after found open at pregnancy checks. Replacement heifers and lactating cows in which AI occurred 41 ± 1 day earlier were presented every 2 to 3 weeks for a pregnancy check by ultrasonography. Ovaries were scanned, follicles were mapped and sized, presence of corpus luteum was noted, and GnRH was injected (day 0) . Females received PGF2" 7 days later (day 7) and then were assigned randomly to either receive estradiol cypionate (ECP) 24 hours after PGF2" (day 8; Heatsynch; n = 230) or a second GnRH injection after PGF2" (day 9; Ovsynch; n = 224). Those detected in estrus were inseminated, whereas the rest received a timed AI (TAI) between 65 and 74 hours after PGF2". Few females (5.1%) were inseminated between open diagnosis and day 8. On day 10, more ECPthan GnRH-treated females were inseminated after detected estrus (24 vs. 6%). Overall, more Ovsynch than Heatsynch females received a TAI (82 vs. 62%). Conception rates tended to be greater for females inseminated after estrus (37%) than after TAI (29%), and the tendency was more pronounced for those treated with Heatsynch (41 vs. 27%) than for those treated with Ovsynch (33 vs. 31%). Conception rates for females having elevated progesterone 7 days after the not-pregnant diagnosis were greater than conception rates of those having low progesterone in Heatsynch (42%; n = 133 vs. 25%; n = 55) and Ovsynch protocols (33%; n = 142 vs. 15%; n = 45). Conception rates were greater in heifers than in lactating cows (43 vs. 28%), regardless of protocol employed. Although overall pregnancy outcomes were similar in response to either the Ovsynch or Heatsynch protocol, inseminations performed after detected estrus before the scheduled TAI reduced days to eventual conception and tended to increase conception rates, particularly after Heatsynch.
Keywords: Dairy; Synchronized estrus; Ovulation; Cysts